2018
DOI: 10.1080/13685538.2018.1439911
|View full text |Cite
|
Sign up to set email alerts
|

Should information about sexual health be included in education directed toward men with cardiovascular diseases?

Abstract: Cardiac patients with ED know more about risk factors for CVD than ED. It is necessary to include information about the negative impact of modifiable risk factors on sexual health into education programs promoting healthy lifestyles in men with cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…One would expect that the accumulation of risk factors could be linked to patients’ socioeconomic factors, insofar as a lower status could indicate a lack of awareness of their negative influence on sexual functioning and the resulting lack of need to address them. However, Kałka et al (2018) showed in a group of 417 men at a mean age of 61.10 ± 9 years with CVD and ED that both a higher education ( p < .0001) and a higher economic status ( p < .0004) were significantly correlated with a higher number of known risk factors for ED.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One would expect that the accumulation of risk factors could be linked to patients’ socioeconomic factors, insofar as a lower status could indicate a lack of awareness of their negative influence on sexual functioning and the resulting lack of need to address them. However, Kałka et al (2018) showed in a group of 417 men at a mean age of 61.10 ± 9 years with CVD and ED that both a higher education ( p < .0001) and a higher economic status ( p < .0004) were significantly correlated with a higher number of known risk factors for ED.…”
Section: Discussionmentioning
confidence: 94%
“…It should be kept in mind that the patients analyzed in this group had atherosclerosis, and a substantial number of them did not present with any significant past coronary incidents. In such patients, the presence of ED is caused by restrictions that result from the underlying disease, such as a substantially limited exercise tolerance, a lowered left ventricular ejection fraction, pharmacotherapy for IHD, or hormonal changes (Kałka, Karpiński, et al, 2017; Kałka et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Of all the factors connected with ED, the patients were least informed on the effect of leisure-time physical activity on penile erection. 61 , 62 The men themselves do not draw the parallel that physical activity reduces both their arteriosclerosis and at the same time their (risk of developing) vascular ED. Therefore, cardiac HPs are recommended to address how and why the PAVED intervention works.…”
Section: Discussionmentioning
confidence: 99%
“…The lower interest in sexual health among patients with ED may result from too little knowledge about the nature of ED and a lack of motivation to fight for improvement in sexual function. 6 13 Shabsigh et al . 24 drew attention to the low awareness of the occurrence of ED.…”
Section: Discussionmentioning
confidence: 99%
“…The study is a part of the PREVANDRO project as an introduction to targeted education aimed at educating patients on risk factors for ED, its main symptoms, possible therapeutic methods, as well as lifestyle modifications, with the aim of fulfilling the recommendations included in the European documents regarding cardiovascular disease prevention. 3 6 12 13 The education was performed by using a PowerPoint presentation, traditional printed materials (brochures, IIEF-5 questionnaire), and a website (www.kardioseksuologia.pl). The educational activities between 2011 and 2018 have reached 17 942 patients.…”
Section: Methodsmentioning
confidence: 99%